(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the role of Robinia pseudoacacia (white acacia) shelterbelts in protecting agricultural areas from wind erosion, dust, soil degradation and microclimate changes. The article describes the agroforestry parameters of this species, agrotechnical aspects of establishing plantations around croplands, environmental and economic advantages, and practical suggestions. The results of the study show that the use of Robinia in planning shelterbelts is effective, taking into account climate, soil and intended use.